High-resolution tracking of hyrax social interactions highlights nighttime drivers of animal sociality - Camille N. M. Bordes; Rosanne Beukeboom; Yael Goll; Lee Koren; Amiyaal Ilany (Communications Biology, 2022)
Proximity sensors reveal that rock hyraxes are more socially selective at night, but nighttime social networks can predict daytime associations.